Pardaxin, a Fish Antimicrobial Peptide, Exhibits Antitumor Activity toward Murine Fibrosarcoma in Vitro and in Vivo - Wu, Shu-Ping (MDPI, 2012)
The antitumor activity of pardaxin, a fish antimicrobial peptide, has not been previously examined in in vitro and in vivo systems for treating murine fibrosarcoma. In this study, the antitumor activity of synthetic pardaxin was tested using murine MN-11 tumor cells as the study model. We show that pardaxin inhibits the proliferation of MN-11 cells and reduces colony formation in a soft agar assay. Transmission electron microscopy (TEM) showed that pardaxin altered the membrane structure similar to what a lytic peptide does, and also produced apoptotic features, such as hollow mitochondria, nuclear condensation, and disrupted cell membranes. A qRT-PCR and ELISA showed that pardaxin induced apoptosis, activated caspase-7 and interleukin (IL)-7r, and downregulated caspase-9, ATF 3, SOCS3, STAT3, cathelicidin, p65, and interferon (IFN)-γ suggesting that pardaxin induces apoptosis through the death receptor/nuclear factor (NF)-κB signaling pathway after 14 days of treatment in tumor-bearing mice. An antitumor effect was observed when pardaxin (25 mg/kg; 0.5 mg/day) was used to treat mice for 14 days, which caused significant inhibition of MN-11 cell growth in mice. Overall, these results indicate that pardaxin has the potential to be a novel therapeutic agent to treat fibrosarcomas.